Performance analysis of underground power cables configuration with different backfill materials - Ramani, Anis Niza; Abdullah, Nur Syahirah; Arfanuddin, Muhammad Ammar; Baharin, Kyairul Azmi; Tarmizi, Aine Izzati (ECTI Association, 2025)
The fundamental construction of power cables gets more complex as transmission power range and voltage increase because they must be built to withstand higher strength and heat buildup. A dependable electrical system with a long operating lifetime will be made possible by adequately installing underground cables. This paper investigates the performance analysis of cable laying configuration in the duct. The temperature distribution of underground cables based on the finite element method (FEM) in the Heat Transfer in Solids (ht) module was analysed using COMSOL Multiphysics software. This study investigated the relationship between different types of cable backfill material and the cable's temperature distribution. Besides, this study analysed the influence of different cable cross-sectional areas and duct types on temperature distribution based on different backfill materials. The proposed materials for cable backfill were air, sand, and fluidized thermal backfill (FTB). Each material has a different value of thermal conductivity. The investigation was conducted with constant boundaries such as cable depth, type of cables, and cable laying position. Simulation results indicate that sand and FTB perform comparably well as backfill materials, and high-density polyethylene (HDPE) duct perform marginally better than polyvinyl chloride (PVC) duct.